Anti-Inflammatory Activity of Calophyllum inophyllum Fruits Extracts - Ilham, Zul (Elsevier, 2014)
In the present work, we are reporting the isolation. characterisation and bioactvity of inophyllums, xanthones and other compounds found in the fruits of Callophyllum inophyllum. In-vitro assays demonstrated that the crude extract at concentration of 50 Pg/ml inhibited 77% and 88% cyclooxygenase and lipooxygenase activities, respectively, indicating its potential as antiinflamatory agent. Phytochemical studies was also conducted on the fruits. Inophyllum A, inophyllum C, inophyllum E, calophylloide, calophynic acid, 11,12-anhydroinophyllum A, 1,7-dihydroxy-6-methoxyxanthone, potocatechuic acid, gallic acid, n-nonacosane, E-sitosterol and sitosterol-3-O-E-D-glucopyranoside were isolated and idetified. On the HPLC chromatogram, at least 18 compounds can be detected.